Keep Your Distance, Wear a Mask and Stay Safe: The Visual Language of Covid-19 Print-Based Signage. (2nd July 2020) - Abdulla, Danah
Abstract : A pandemic introduces multiple factors that must be communicated to the public. The coronavirus outbreak has demonstrated the necessity of effective risk communication during a global pandemic and the importance of communication design within this process. Since March 2020, official and ad-hoc signage reminding the public to keep their distance, wear a mask, stay safe and stay at home have become ubiquitous in cities all over the world. This paper analyses the visual language of COVID-related signage – those made by designers and those made without – in London, UK from April 2020 to January 2021. A mixture of compositional interpretation and semiology was performed on 130 photographs of print-based signage to categorise them under themes. Results were categorised these under four broad themes: Thank you, Togetherness, Care; Safety and Security; Heroes and Protection; and Fear, Danger, Caution. The findings invite readers to reflect on the effectiveness of the visual communication strategy and ask who these designs are for.